Vascular gastric anomalies as a cause of relapsing bleeding - Golubović Gradimir; Kiurski Milosav; Špica Vladimir; Tomasević Ratko; Pavlović Aleksandar; Đukić Nikola (Vojnosanitetski Pregled)
Background. Although relatively rare, gastric vascular anomalies can be recognized as a source of both chronic and acute blood loss, most often presenting as long term iron deficiency anemia, rarely as severe acute gastrointestinal bleeding. Case report. We present five patients with various gastric vascular anomalies, diagnosed during the year of 2003. in the Clinical Hospital Center Zemun. The diagnosis was based on endoscopic appearances, clinical history and characteristic histological findings. Gastric vascular anomalies presented in our review were: portal hypertensive gastropathy, gastric antral vascular ectasia, angiodysplasia, hereditary hemorrhagic telangiectasia and Dieulafoy lesion. The used treatment modalities included surgery and various endoscopic techniques (schlerotherapy, argon plasma coagulation). Conclusion. Patients presented with chronic iron deficiency anemia or acute and recurrent gastrointestinal hemorrhage should be considered as having one of gastric vascular anomalies.